THE EFFECT OF FINANCIAL PERFORMANCE AND CORPORATE SOCIAL RESPONSIBILITY (CSR) ON THE VALUE OF CEMENT COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) IN THE PERIOD 2020-2024 - Rita J D Atarwaman; Kezia S Souhoka; Nailah Atmaranti Salim Huath; Devin Wacanno (PT. Jurnal Center Indonesia Publisher, 2026)
This study examines the effect of financial performance and Corporate Social Responsibility (CSR) on firm value in cement companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. Financial performance is proxied by Return on Assets (ROA), while firm value is measured using Price to Book Value (PBV). CSR is measured through a disclosure index based on the Global Reporting Initiative (GRI) Standards using content analysis. This research employs a quantitative associative approach with secondary data obtained from annual reports and sustainability reports of seven cement companies. Multiple linear regression analysis is used to test the hypotheses. The results indicate that ROA has a positive and significant effect on firm value, suggesting that efficient asset utilization enhances market perception. CSR disclosure also shows a positive and significant effect on firm value, supporting the legitimacy theory that socially responsible practices strengthen corporate reputation and investor confidence. These findings highlight the importance of integrating financial performance and sustainability strategies to enhance firm value, particularly in capital-intensive and environmentally sensitive industries such as cement.